Analisis Budaya Kerja dan Employee Engagement - Ferdy Yanuar; Rusman Frendika (Bandung Conference Series: Business and Management, 2023)
Abstract. The purpose of this research is to find out the differences in work culture and Employee Engagement between Sundanese & Javanese employees at PT. Sarimelati Kencana Tbk. This study uses a comparative descriptive method using a quantitative approach. In determining the sample in this study, using cluster sampling technique and totaling 40 samples. And the data collection technique used is a questionnaire, questionnaire distributed to employees who fall into the testing criteria. From the results of statistical calculations, it is calculated that there is no significant difference in the work culture of the Sundanese and Javanese, but it is evident from the results of the description that the difference is obtained, but it is not considered a significant difference because it refers to the company's work culture. In the work culture variable, the average value of the work culture of Javanese employees is higher than that of the Sundanese. However, on the item description data, it is shown that the regulatory indicators and values indicate that Sundanese employees have a higher level of discipline, initiative and honesty level than the Javanese with a comparison value of 90.92% and 77.78%. . In the employee engagement variable, the average value of employee engagement of Javanese employees is higher than that of Sundanese. In the item description data, it is shown that the pride indicator shows that Javanese employees have a higher level of enthusiasm, pride, and happiness levels than Javanese employees with a comparison value of 83.33% and 68.18%. Abstrak. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan budaya kerja dan Employee Engagement antara karyawan Sunda & Jawa di PT. Sarimelati Kencana Tbk. Penelitian ini menggunakan metode deskriptif komparatif dengan menggunakan pendekatan kuantitatif. Dalam menentukan sampel dalam penelitian ini, menggunakan teknik cluster sampling dan berjumlah 40 sampel. Dan teknik pengumpulan data yang digunakan adalah kuesioner, kuesioner dibagikan kepada pegawai yang masuk dalam kriteria pengujian. Dari hasil perhitungan statistik dihitung tidak terdapat perbedaan yang signifikan pada budaya kerja orang sunda dan jawa, namun terbukti dari hasil deskripsi diperoleh perbedaan yang signifikan, namun tidak dianggap perbedaan yang signifikan. karena mengacu pada budaya kerja perusahaan. Pada variabel budaya kerja rata-rata nilai budaya kerja pegawai Jawa lebih tinggi dibandingkan dengan pegawai Sunda. Namun pada data deskripsi item terlihat bahwa indikator dan nilai peraturan menunjukkan bahwa pegawai suku Sunda memiliki tingkat kedisiplinan, inisiatif dan kejujuran yang lebih tinggi dibandingkan pegawai suku Jawa dengan nilai perbandingan 90,92% dan 77,78%. . Pada variabel employee engagement, nilai rata-rata employee engagement karyawan Jawa lebih tinggi dibandingkan karyawan Sunda. Pada data deskripsi item terlihat bahwa indikator kebanggaan menunjukkan bahwa pegawai Jawa memiliki tingkat antusiasme, kebanggaan, dan kebahagiaan yang lebih tinggi daripada pegawai Jawa dengan nilai perbandingan 83,33% dan 68,18%.